Potential of Tyrosine Kinase Receptor TIE-1 as Novel Therapeutic Target in High-PI3K-Expressing Ovarian Cancer - Zhang, Xuewei (Cancers (Basel), 2020)
Tyrosine kinase receptor TIE-1 plays a critical role in angiogenesis and blood-vessel stability. In recent years, increased TIE-1 expression has been observed in many types of cancers; however, the biological significance and underlying mechanisms remain unknown. Thus, in the present study, we investigated the tumor biological functions of TIE-1 in ovarian cancer. The treatment of SKOV3 ovarian-cancer cells with siRNA against TIE-1 decreased the expression of key molecules in the PI3K/Akt signaling pathway, such as p110α and phospho-Akt, suggesting that TIE-1 is related to the PI3K/Akt pathway. Furthermore, the knockdown of TIE-1 significantly decreased cell proliferation in high-PI3K-expressing cell lines (SKOV3, CAOV3) but not low-PI3K-expressing cell lines (TOV112D, A2780). These results suggested that inhibition of TIE-1 decreases cell growth in high-PI3K-expressing cells. Moreover, in low-PI3K-expressing TOV112D ovarian-cancer cells, TIE-1 overexpression induced PI3K upregulation and promoted a PI3K-mediated cell proliferative phenotype. Mechanistically, TIE-1 participates in cell growth and proliferation by regulating the PI3K/Akt signaling pathway. Taken together, our findings strongly implicate TIE-1 as a novel therapeutic target in high-PI3K-expressing ovarian-cancer cells.